Notions of shock and attention in Tik Tok videos - Erthal, Cláudia (Revista GEMInIS, 2022)
This work seeks to understand how and if the entertainment experience obtained by watching videos on the Tik Tok social platform that uses editing and design tools, such as distortion filters for physical appearance and voice, is an immersive experience that causes a Shock to the user as seen in Walter Benjamin. And if the social network has created daily increasing the number of accesses, seeking to retain the media user and seem to attempt to lead the user to an Attention Economy system described by Jonathan Crary. Platforms that work with such design are also guided by the hands of users with content creation to Shock an audience immersed in what is called Snack Culture by Scolari. As for a culture that develops a sensorial audio-visual content format, these contents provoke a sensory effect, a brief experience within a platform design that can create a dynamic between playful and entertainment. This text is built applied to the communicational practice of the use of platforms and is an attempt to understand the contemporary media paths that are outlined with the platform of culture.